The Roman Imperial Cult and Revelation - Naylor, Michael P. (Currents in biblical research, 2010)
The question of the relationship of the Roman Imperial Cult and Revelation has occupied the attention of scholars throughout the past one hundred years. During this time, major shifts have taken place both in the assessment of the Roman Imperial Cult in the context of the Roman Empire and in the interpretation of its role with respect to the book of Revelation. This article surveys and assesses these trends. It begins with a discussion of studies on the Roman Imperial Cult from the standpoint of classical studies. Next, texts within Revelation typically cited as indicating a response to emperor worship are introduced. The third and final section focuses upon studies on Revelation, with particular focus given to interpretive approaches, Christology, and the question of persecution under Domitian.